Tác động của CSR và Marketing đến đổi mới lao động của SMEs ở Việt Nam: Tiếp cận trên biến nội sinh Networking - Từ Văn , Bình; Ngô Giang , Thy; Huỳnh Đăng , Khoa; Nguyễn Đình , Thông (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Applying the Extended Regression Model (ERM) on the sample of 2,649 Small and Medium Enterprise (SMEs) in Vietnam, the results found are very interesting: (i) Networking plays an endogenous role in influencing the positive impact of Corporate Social Responsibility (CSR) and marketing on labor innovation of SMEs; (ii) The increased number of communication of SME owner to stakeholders creates positive opportunities for labor innovation, which it is not excluded enterprises with a long or short length of stay in market; (iii) Due to financial conditions SMEs have a mixed investment between CSR and marketing. That is, if CSR gets more attention, marketing investment will decrease, or marketing gets more attention, CSR will get less investment; and (iv) The role of the endogenous variable of networking is seen more clearly for SMEs with large labor size manufacturing enterprises, which the sector of food industry SMEs are taken into.